If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + -6x = 11 + -18 Reorder the terms: 2(-3 + x) + -6x = 11 + -18 (-3 * 2 + x * 2) + -6x = 11 + -18 (-6 + 2x) + -6x = 11 + -18 Combine like terms: 2x + -6x = -4x -6 + -4x = 11 + -18 Combine like terms: 11 + -18 = -7 -6 + -4x = -7 Solving -6 + -4x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -4x = -7 + 6 Combine like terms: -6 + 6 = 0 0 + -4x = -7 + 6 -4x = -7 + 6 Combine like terms: -7 + 6 = -1 -4x = -1 Divide each side by '-4'. x = 0.25 Simplifying x = 0.25
| -[9x(2x+6)]=-3-[4(3x-4)-3x] | | 9+6n=6n^2 | | 10/2=x+1/3 | | n-(12-n)=38 | | n*5.06=506.00 | | x^2+y^2-4x-8y+20=0 | | y-2=-4(x-1) | | 20-2p=5+3p | | .83333333333333333x-3=.625x+7 | | v+5/4=3/6 | | -2(3n-6)=-6 | | 2330100+x=2.1*(863000+x) | | 2(-c-12)=-2c-12 | | 17+4j=125 | | 10/5=4/x | | 14+20=28+13-13 | | 8+9=15y-5-14y | | x-.15x=180 | | 1.6h-72=30-4h | | .83x-3=.625x+7 | | (3x+6)+(x+2)+(x+2)+(3x+6)= | | 6519.8+150.99w=3500 | | 16-3x=6x+7 | | 48k=-276 | | 6x(2)+1-n+5n(2)= | | 6519.88-150.99w=3500 | | 3z+8=13+3x-z | | -2a-9=6a+5 | | 3500-150.99w=-6519.88 | | 2+2x+7=-6 | | 20+14=28+13 | | -49+3k=k-5k |